1984
DOI: 10.1002/bbpc.198400053
|View full text |Cite
|
Sign up to set email alerts
|

Rate Constants and Vinoxy Product Yield in the Reaction OH + Ethylene Oxide

Abstract: Chemical Kinetics / Elementary Reactions / Laserinduced Fluorescence / RadicalsAbsolute rate constants and the vinoxy (CHzCHO) product yield for the reaction of OH radicals with ethylene oxide (C ZH40) have been determined using a combined laser photolysis/resonance fluorescence (laser induced fluorescence) technique. The rate constant for OH decay is k l = (1.1 ± 0.4)' 10-1I exp[ -(1460 ± 150) K/T] cm 3/s over the temperature range T = 298 -435 K. The branching ratio for vinoxy (VO) formation at 298 K is foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…If our result k~ = 830 +-100 s -1 is solely attributed to reaction (2), we obtain k2 = (4-+ 0.5) 10 -12 cma/molecule, s in reasonable agreement with direct studies of this reaction (Fritz et al, 1984)which gave k2 = (6.5---2) 10 -1~ cm3/ molecule • s. In principle, LIF profiles of the temporal behaviour of a reaction product can also be used to derive the branching ratio or yield of this particular product relative to the overall consumption of reagents (i.e. H~gele et aI., 1983;Lorenz and Zellner, 1984). This method, however, requires the absolute calibration of the fluorescence intensity including a measure of the quenching behaviour of all components of the reaction mixture.…”
Section: Lif Measurementssupporting
confidence: 83%
“…If our result k~ = 830 +-100 s -1 is solely attributed to reaction (2), we obtain k2 = (4-+ 0.5) 10 -12 cma/molecule, s in reasonable agreement with direct studies of this reaction (Fritz et al, 1984)which gave k2 = (6.5---2) 10 -1~ cm3/ molecule • s. In principle, LIF profiles of the temporal behaviour of a reaction product can also be used to derive the branching ratio or yield of this particular product relative to the overall consumption of reagents (i.e. H~gele et aI., 1983;Lorenz and Zellner, 1984). This method, however, requires the absolute calibration of the fluorescence intensity including a measure of the quenching behaviour of all components of the reaction mixture.…”
Section: Lif Measurementssupporting
confidence: 83%
“…The analogous vinoxy radical plays a major role in the gasphase oxidation of unsaturated hydrocarbons and is an important intermediate in combustion and photochemical smog cycles . And C 2 H 3 O radical is interesting because it has two electronic states in the ground state, and both experiment and ab initio calculations have confirmed that fact.…”
Section: Introductionmentioning
confidence: 99%
“…Both of which represent potential reasons why the onset of negative temperature dependence occurs at a higher temperature for Reaction (1) than with other epoxides. A further effect may come from an increase in the rate of vibrational relaxion that is afforded to molecules of a larger size, which would explain why the reaction of OH with ethylene oxide shows no negative temperature dependence within the temperature range that it has been studied so far [10].…”
Section: Resultsmentioning
confidence: 99%
“…Cyclohexene oxide (1,2-epoxycyclohexane) is larger than those epoxides studied previously [10][11][12][13], and, by virtue of the fact that it contains more C-H bonds than other epoxides found in the kinetic database [9], is expected to react comparatively rapidly with OH and be lost primarily through Reaction (1) under atmospheric conditions. The bicyclic structure of cyclohexene oxide also contrasts with previously studied epoxides, and may influence its reaction with OH.…”
Section: Introductionmentioning
confidence: 95%